The influence of complexity, perceived benefits, social influence, and demographics on adoption of Internet banking in Tanzania - Lyimo, Victor; Dev, Jani (University of Dar es Salaam Library Journal, 2021)
This study aimed at testing the influence of perceived benefits, social influence, technological complexity, and demographic variables in the adoption of internet banking in Tanzania. Using a structured questionnaire, convenient and quota samples of bank customers was used that yielded 400 dully filled questionnaires with 200 for those who are using internet banking and 200 who have not adopted the use of internet banking with binary regression used to test the hypotheses. Binary logistic regression results successfully classifying bank customers internet usage by 75.8% after inclusion of perceived benefits, social influence and complexity. An addition of only 3.7% accuracy in classifying bank customers arises after the inclusion of demographic variables. The results indicate complexity, perceived benefits, and social influence to contribute positively in the adoption of internet banking. The finding provides practical implications to commercial banks on how to promote internet banking effectively and efficiently that will enhance financial inclusion of the population in African developing economies context. Theoretically, the study incorporates and integrates variables into the common models used to explain internet adoption.